Analisis Implikasi Perceraian Asing terhadap Hak atas Tanah berdasarkan Putusan No. 19/Pdt.G/2014/PN.Sgr. dan Perjanjian Pra-Perkawinan sebagai Solusi Penyelesaian - Diva Raniza; M. Indra Pratama; Roger Alfiano; Rizha Claudilla Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This paper explores the involvement of International Civil Law in the implications of foreign divorce on land rights by paying attention to the principles contained in International Civil Law. In terms of writing, the author will analyze Decision No. 19/Pdt.G/2014/PN.Sgr. as a review of facts that will be analyzed in accordance with the scope of International Civil Law using relevant research methods. The author reviews that the research method used to compile this writing is juridical-normative based on the applicable laws and regulations and in accordance with what is the subject of discussion. In addition, this paper also pays attention to the theory of legal protection by Philipus M. Hadjon and the principles contained in International Civil Law as supporting aspects in the preparation of this analysis. To strengthen the argument, the author also compares several provisions related to the status of land ownership by foreign parties and the application of pre-marriage agreements as an alternative settlement. The final result of this writing will highlight the correctness of the judge's decision based on the author's analysis and provide suggestions that are considered relevant as solutions that can be offered.